Evolutionary Relationships among Boulengerella Species (Ctenoluciidae, Characiformes): Genomic Organization of Repetitive DNAs and Highly Conserved Karyotypes - Souza E Sousa, José F. de; Viana, Patrik Ferreira; Bertollo, Luiz Antônio Carlos; Cioffi, Marcelo de Bello; Feldberg, Eliana (Cytogenetic and Genome Research, 2017)
Ctenoluciidae is a Neotropical freshwater fish family whose representatives are known as bicudas. The genus Boulengerella contains 5 species, and 4 of them (B. cuvieri, B. lateristriga, B. lucius, and B. maculata) were cytogenetically analyzed in the present study by conventional and molecular procedures. All 4 species have a very similar karyotype, with 2n = 36 chromosomes (14 metacentrics + 16 submetacentrics + 6 subtelocentrics; FN = 72). However, the heterochromatin distribution pattern is species-specific. In all 4 species, the nucleolus organizer region is located in pair 18, as also confirmed by cytogenetic mapping of 18S rDNA. In turn, 5S rRNA genes are present in 2 chromosome pairs: in pair 1 of all 4 species, and in pair 10 of B. lateristriga, B. maculata, and B. cuvieri, but in pair 4 of B. lucius. The telomeric probe highlighted terminal regions in all chromosomes, as well as an interstitial centromeric sequence in pair 3 of the 3 first-mentioned species. Notably, a conspicuous heteromorphic secondary constriction in chromosomes 18 was found only in the males of the 3 species, rendering one of the homologs much larger than the other one. This feature, associated with a large 18S rDNA block and accumulation of telomeric sequences, suggests the presence of an XX/XY sex chromosome system in the analyzed Boulengerella species. © 2017 S. Karger AG, Basel.
Keywords: Dna 18s; Repetitive Dna; Rna 5s; Ribosome Dna; Rna 18s; Rna 5s; Animals Experiment; Bioaccumulation; Boulengerella Cuvieri; Boulengerella Lateristriga; Boulengerella Lucius; Boulengerella Maculata; Characiformes; Chromosome 18; Chromosome Analysis; Chromosome Nor; Chromosome Painting; Conserved Sequence; Controlled Study; Ctenolucius Beani; Ctenolucius Hujeta; Cytogenetics; Female; Genome Analysis; Heterochromatin; Karyotype; Karyotype 46,xx; Karyotype 46,xy; Male; Evolution, Molecular; Nonhuman; Priority Journal; Sequence Analysis; Sex Chromosome; Species Difference; Animals; Characiformes; Chromosome Banding Pattern; Classification; In Situ Hybridization, Fluorescence; Genetics; Genome; Karyotyping; Evolution, Molecular; Nucleotide Repeat; X Chromosome; Y Chromosome; Animal; Characiformes; Chromosome Banding; Conserved Sequence; Ribosomal Dna; Evolution, Molecular; Female; Genome; In Situ Hybridization, Fluorescence; Karyotyping; Male; Repetitive Sequences, Nucleic Acid; Rna, Ribosomal, 18s; Rna, Ribosomal, 5s; X Chromosome; Y Chromosome